Onion Yield Prediction Based on Machine Learning - et. al., A. Selvi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Indian economy is mostly based on agriculture but the price of each vegetables and fruits varies in day today life. In recent days, the price of onion is increasing wisely, to predict the future price of onion by using past data and also the water level need for a particular crop using current dataset and also by using climate changes. Using Machine learning, collect the dataset of weather report and past and current priceof vegetables (e.g. onion) and water level prediction of plants. By analyzing these dataset the price of vegetables and the water level required for particular plant on particular day according to the climate change are analyzed and predicted. By using machine learning algorithm like Support vector machine, stemming, and tokenization. This will be helpful for the cultivators to crop a plant according to the weather and it will be useful when the water level needed for the particular plant is known previously. And these will also help to bring customer and farmer will gain more. The water level will also help to enhance the harvest yield and also will produce good crops all the time. The cultivator will gain more and the harvesting will also be more when compared to other systems.